THE EFFECT OF QUALITY COST ON THE RATTAN INDUSTRY PERFORMANCE - Evi Yuniarti; Artie Arditha; Nurmala Nurmala (Saburai International Journal of Social Sciences and Development, 2018)
The purpose of the study is to determine the quality of products in the industrial competitiveness of rattan industry in South Lampung. The technique data used mostly resulted from the interview. To improve the credibility of research findings, the other methods of data collection were used, such as questionnaires, direct observation and document analysis and records. This study is descriptive verificative with explanatory survey. The method of data analysis is path of analysis. The object of the study is the cost of quality which consists of prevention costs, appraisal costs, internal failure costs, and external failure costs. The results showed that the cost of quality activities consisting of prevention activities, control activities, internal failure activities, and external failure activities had a significant effect on the performance of the rattan industry in southern Lampung.